Evaluating the Effectiveness of Japanese Business Manner Education Using Council System Group Evaluation of - Fujihara, Yumi (Archives of Business Research, 2018)
In Japan, career education is obligatory for all students at universities and other institutions of higher education, and attention is currently being directed at the Fundamental Competencies for Working Persons, which are the basic abilities required to work together with various people in the workplace and in local communities as advocated by the Japanese Ministry of Economy, Trade and Industry (METI). At the same time, undergraduate education is being reconsidered from the standpoint of ensuring quality, and there have been more requests to conduct and measure the effects of educational programs on general-purpose, basic abilities in the modern workplace. Accordingly, this research focused on Japanese business manner education, which comprises manner education on the knowledge and skills related to a given occupation, as one facet of career education. It proposed a new Council System (CS) Group Evaluation method, based on the Japanese council system, which is a general decision-making method in Japanese business, for role-playing group work on Japanese business manners. In this study, this method was implemented for the multilateral verification of effects from the viewpoint of the Fundamental Competencies for Working Persons. As a result, we statistically confirmed the effects of peer evaluation and CS Group Evaluation on the Fundamental Competencies for Working Persons in business manner education, based on the results of questionnaire surveys administered to 210 students over a two-year period. Finally, it specified such future issues as the necessity for expanded, continual research on the generalizability of these results, as well as elucidating what elements of CS Group Evaluation effect the improvement of the Fundamental Competencies for Working Persons.